Development of a Universal Disease-Specific Outcome Instrument for Spine Trauma Patients – the AOSpine Patient Reported Outcome Spine Trauma (AOSpine PROST). Issue 1 (April 2016) - Sadiqi, Said; Lehr, A. Mechteld; Post, Marcel W.; Oner, F. C.
Introduction: In the absence of an outcome instrument specifically designed and validated for traumatic spinal column injury patients, it is difficult to measure the effect size of various treatment options in a variety of traumatic spinal column injuries. In reflection of this dilemma, the AOSpine Knowledge Forum Trauma initiated a project to develop and validate universal disease-specific outcome instruments for adult spine trauma patients that include both the patients' and clinicians' perspective. The International Classification of Functioning, Disability and Health (ICF) is used as the basis for the patient reported part of this outcome instrument, named AOSpine Patient Reported Outcome Spine Trauma (AOSpine PROST). Material and Methods: Based on the results of 4 preparatory studies and a consensus conference using the ICF methodology, 25 ICF categories were selected as core categories for patient reported outcome measurement in adult traumatic spinal column injury patients. The response scale for use agreed on was the Numeric Rating Scale 0–100, with 0 indicating no function at all and 100 indicating the pre-injury level of function. These results formed the basis for the development of the AOSpine PROST. The first draft of the Dutch version was pilot tested among a consecutively selected representative sample of 25 traumatic spinal column injury patients from a level-1 trauma center in the Netherlands. The 'think aloud' and 'probing' methods were used to evaluate the comprehensibility, relevance, acceptability, feasibility, and completeness of the AOSpine PROST. Subsequently, this draft version was cross-culturally translated and adapted into English according to established guidelines. This process consisted of multiple stages, including forward-translations, synthesis, back-translations, and an expert committee meeting to reach consensus on any discrepancies and to develop a final English version of AOSpine PROST. Results: Out of the 25 core ICF categories, 9 related to body functions, 14 related to activities and participation, and 2 related to environmental factors . Implementing those 25 core categories into the selected response scale resulted in a draft version of AOSpine PROST, consisting of the following 19 items: household activities, work/study, recreation and leisure, social life, walking, travel, changing posture, maintaining posture, lifting and carrying, personal care, urinating, bowel movement, sexual function, emotional function, energy level, sleep, stiffness, loss of strength, and pain. Very satisfactory results were obtained from the pilot study, and only some minor adaptions were needed. Statistical analysis showed a high level of internal consistency (Cronbach's α = 0.926). Conclusion: Using the ICF methodology and based on the results of 4 different preparatory studies and a consensus conference, a disease-specific patient reported outcome instrument for traumatic spinal column injury patients has been developed. Very good results were obtained from a pilot study, and currently the Dutch and English versions of AOSpine PROST are being subjected to further validation in an international multicenter study. Ultimately, the AOSpine PROST will be a helpful tool to compare various treatments and improve the quality of health care.